The Better Resurrection (Heb. 11:35): A Key to the Structure and Rhetorical Purpose of Hebrews 11 - Cockerill, Gareth Lee (Tyndale bulletin, 2000)
This study demonstrates through a detailed study of Hebrews 11 that references to future resurrection (11:17-19 and 11:35) are of foundational importance to the structure and logic of the argument of the chapter, and thus to the faith encouraged by the author in this chapter. This further suggests that the common assumption that the resurrection of Christ was of no importance to the author of Hebrews is mistaken.